Exploring travelers’ willingness to pay for green hotels in the digital era - Galati, Antonino; Thrassou, Alkis; Christofi, Michael; Vrontis, Demetris; Migliore, Giuseppina (My University, 2021)
The past few years have witnessed an intensifying effort by hotels to respond to customers’ growing environmental sensitivities. A critical aspect of this market trend is the actual willingness of tourists to pay (WTP) for green products and services offered by green hotels. Previous studies in this research field have mainly focused on the relationship between guests’ attitudes and their behavioral intentions, neglecting the influence of external and situational factors. In light of this, the present paper contributes to knowledge by analyzing the influence of e-Word-of-Mouth (e-WOM) and physical image, as it emerges from digital platforms, and the effect of green hotel attributes on the travelers’ WTP for green hotels. Methodologically, the research is experimental and is based on a survey of 251 travelers who stayed at hotels in Italy. The findings revealed a positive and significant relationship of e-WOM valence, physical image, consumers’ income, and green attributes related to the sustainable transport services offered, on the WTP of tourists for a green hotel. The findings, as well as enriching the literature on green hotels, can guide practitioners to develop effective communications tools on website and social media platforms to enhance the green image of hotels.
Keywords: Digital platform; e-WOM; Green attributes; Green image; Psychological determinants; Sustainable tourism